RESERVOIR STEAM FLOOD MODELING BASED ON 4D SEISMIC AND ROCK PHYSICS - Muhammad Edisar; Usman Malik (Komunikasi Fisika Indonesia, 2014)
Reservoir steam flood modeling based on Time Lapse (4D) seismic and Rock Physics data was constructed in Pelangi oil field on central Sumatra Basin. Model used to monitoring and tracking steam flood and production related changes in the reservoir. A model of the reservoir steam flood was constructed for a pattern steam flood in Area X of the field. The model was based on a geostatistical geological model and populated with temperature and porosity. Pressure and saturation properties were added to provide the necessary input for seismic modeling. Through a rock physics model based on the core analysis, the elastic properties (Vp, Vs and density) were determined. These elastic properties were used to determine the seismic response of the model with and without steam flood.The results of the model indicated, that from the rock physics modeling using Gassmann equation, steam flood decreases the Vp by an average of 20-25% in the reservoir sands. Rock physics analysis also shown that shear velocities are also sensitive to steam flood, with an average decrease of 12%. However, the Gassmann calculation results shown that Vs is insensitive to steam flood. This discrepancy is probably caused by Gassmann's assumptions that no chemico-physical interactions exist between the rocks and pore fluids. Time shifts in seismic modeling events provided an indication of the presence of steam flood in the overlying reservoir. The relationship between time shift and steam thickness was strong for thick steam, but it was not possible to distinguish thin steam zones from thick hot oil zones solely on the basis of time shift. At the same time, tuning between the steams related and geologically related seismic events influenced seismic amplitudes. It appears that a combination of attributes is necessary to resolve the effects of steam on the 4D seismic data acquired over of the field.